Scientific mapping of experimental research on solar cookers: Global trends, evolution, and future directions - Flavio Odoi-Yorke; Bismark Baah; Richard Opoku (Solar Energy Advances)
Solar cooking technologies represent a critical sustainable energy solution for addressing global energy poverty and reducing the environmental impacts of traditional cooking methods. Despite growing research interest, comprehensive systematic bibliometric reviews of experimental research on solar cookers research remain limited. This bibliometric study aims to analyze experimental research on solar cooker trends, technological innovations, and knowledge development from 1994 to 2024. Utilizing the Scopus database, we applied the PRISMA systematic review methodology to analyze 581 peer-reviewed publications. Bibliometric analysis was conducted using R software's Bibliometrix package, examining scientific production, global collaboration patterns, keyword dynamics, and thematic evolution. The study findings reveal a consistent 7.46 % annual growth in experimental research on solar cookers, with significant advancements in thermal performance, energy efficiency, and technological design. India emerged as a research leader with strong international collaborations, particularly in Africa and Latin America. Emerging research themes include phase change materials, thermal energy storage, and innovative collector designs. The analysis identified a progressive shift from fundamental design considerations to more sophisticated, multidisciplinary approaches integrating sustainability, performance optimization, and socio-economic contexts. This comprehensive review provides critical insights into experimental research on solar cooking trajectories, highlighting the field's technological growth and potential to address global energy challenges. The findings emphasize the importance of continued interdisciplinary research and international collaboration in advancing sustainable cooking technologies.